2014
DOI: 10.3389/fnbot.2014.00020
|View full text |Cite
|
Sign up to set email alerts
|

Audio-visual feedback improves the BCI performance in the navigational control of a humanoid robot

Abstract: Advancement in brain computer interfaces (BCI) technology allows people to actively interact in the world through surrogates. Controlling real humanoid robots using BCI as intuitively as we control our body represents a challenge for current research in robotics and neuroscience. In order to successfully interact with the environment the brain integrates multiple sensory cues to form a coherent representation of the world. Cognitive neuroscience studies demonstrate that multisensory integration may imply a gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…Although mostly such stimulations are intended for the generation of brain activity from the corresponding lobes (An et al, 2014; Tidoni et al, 2014; Wu et al, 2016; Xu et al, 2016), some audio/video stimuli are given to generate P300 signals (Rutkowski, 2016). For healthy individuals, these stimulations can be effective in generating multiple commands.…”
Section: Combination Of Brain Signalsmentioning
confidence: 99%
“…Although mostly such stimulations are intended for the generation of brain activity from the corresponding lobes (An et al, 2014; Tidoni et al, 2014; Wu et al, 2016; Xu et al, 2016), some audio/video stimuli are given to generate P300 signals (Rutkowski, 2016). For healthy individuals, these stimulations can be effective in generating multiple commands.…”
Section: Combination Of Brain Signalsmentioning
confidence: 99%
“…Remotely BCI-controlled androids are a promising possibility for the world and for the social interaction of immobilized patients, and the sense of control and responsibility over, for example, limb prostheses and more remote effectors (Tidoni, Gergondet, Kheddar, & Aglioti, 2014), should be a central consideration when developing these systems. This is a topic of high ethical relevance (Yuste et al, 2017), since we should expect in the next few decades a considerable growth of different forms of BCIs that can control anything from a screen cursor to a robot in another continent (Tidoni et al, 2014). A thorough understanding of the responsibility felt for these actions and its neural basis is therefore of the utmost importance.…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…Conveniently, augmented feedback can be used to convey artificial proprioceptive and exteroceptive information 21,29 , which may help to develop strong internal models. Researchers have used audio augmented feedback in both robotic teleoperation 30,31 and Brain Computer Interfaces (BCI) 32 and have concluded that audio augmented feedback improves performance. Unlike visual feedback, audio requires less focus of attention and reduces distraction 33,34 .…”
Section: Introductionmentioning
confidence: 99%